THE EFFECT OF WRITING ANXIETY TOWARD WRITING SELF-EFFICACY ON GRADE EIGHTH STUDENTS AT SMP NEGERI 7 BAUBAU - Lilis Ayu Saputri; Nety Nety (English Education Department, 2022)
Problem Problem statement of this research was whether there was a significant effectof students' writing anxiety on the writing self-efficacyat SMP Negeri 7 Baubau. Objective of the research was to find out whether there was a significant effect of writing anxiety toward writing self-efficacyat SMP Negeri 7Baubau. Data collection in this research was carried out using a research instrument in the form of a questionnaire, to determine the effect of writing anxiety on writing self-efficacy in the use of English. The data obtained were analyzed by descriptive statistical analysis, prerequiset analysis, and inferential statistical analysis. Based on the results of the research, it was concluded that there was no significant effectbetween writing anxiety toward writingself-efficacy. This conclusion is based on statistical analysis. Because Fcount is 3.112.with a significant value of 0.183. the calculated Fcount is lower than Ftable and the significant value is greater than (0.05). This means that the null hypothesis is accepted and the alternative hypothesis is rejected.